2019
DOI: 10.4068/cmj.2019.55.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of I-131 Biokinetics after Recombinant Human TSH Stimulation and Thyroid Hormone Withdrawal Measured by External Detector in Patients with Differentiated Thyroid Cancer

Abstract: The aim of this study was to compare radioactive iodine (I-131) biokinetics after recombinant human TSH stimulation (rhTSH) and thyroid hormone withdrawal (THW) in patients with differentiated thyroid cancer (DTC). External effective dose rates were measured using external detectors and imaged quantitatively at the time of discharge from the isolation wards. We retrospectively analyzed 32 patients who had been diagnosed with DTC, papillary or follicular, and underwent remnant ablation after either rhTSH stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Still, there was a reduced iodine uptake in the abdomen and kidneys during the SNA001 period compared to the THW period, which may lead to increased concentration of iodine in the sites of residual thyroid tissues and metastases ( 21 , 22 ). In addition, other evidence suggests that after rhTSH injection, iodine clearance is faster than THW ( 23 ), which may lead to a decrease in iodine retention in the background. Finally, the effect caused by low dose iodine-131 in the SNA001 administration period may lead to the decrease of iodine uptake capacity during the THW period.…”
Section: Discussionmentioning
confidence: 99%
“…Still, there was a reduced iodine uptake in the abdomen and kidneys during the SNA001 period compared to the THW period, which may lead to increased concentration of iodine in the sites of residual thyroid tissues and metastases ( 21 , 22 ). In addition, other evidence suggests that after rhTSH injection, iodine clearance is faster than THW ( 23 ), which may lead to a decrease in iodine retention in the background. Finally, the effect caused by low dose iodine-131 in the SNA001 administration period may lead to the decrease of iodine uptake capacity during the THW period.…”
Section: Discussionmentioning
confidence: 99%
“…Kalevi et al found that recombinant human TSH stimulation (rhTSH) and thyroid hormone withdrawal (THW) could influence the I-131 biokinetics in patients with differentiated thyroid cancer, and washout of I-131 was faster after rhTSH stimulation than THW. 27 Kasner et al first found that the combination of rhTSH stimulation and nearly adequate withdrawal may help convert more I-131-negative whole-body scans to positive. 28 Cluster 5 was mainly concerned about management guidelines.…”
Section: Discussionmentioning
confidence: 99%